DEFINITION OF BELT CONVEYOR BOUNDARIES AS A PART OF RISK ASSESSMET (Perner's Contacts, 2012)
Belt conveyors are devices which are used to transport pieces or bulk materials on a straight or an inclined transportation paths. During the operation of the conveyor belt, unexpected and undesirable event can happened, as in every daily human activity. These events - negative phenomena are leading to injuries, damages of human health or material. Analysis of negative phenomena is contributing to create appropriate rules to minimize the risk. Risk assessment is not only a legal obligation, but it is a process of increasing safety of work in practice.
Keywords: conveyor belt, risk, limits of the machine